“Se eu morrer e continuarem a minha luta, morro feliz”: a construção do mártir Zé Maria do Tomé (2010-2023) - Reges, Luciana Meire Gomes (2024)
This thesis analyzes the social and political construction of Zé Maria do Tomé as a martyr of the socio-environmental struggle in/in Ceará. José Maria Filho was murdered near his residence, located in Chapada do Apodi, an area of intense land conflict, with twenty-five shots, on April 21, 2010. The death marked by violence of the peasant and community leader put at risk the existence and continuity of the activities of Social Movements that had their agendas aligned with the struggle flags of Zé Maria do Tomé: the expropriation of land, the contamination of water and soil due to indiscriminate use of pesticides. Death is a phenomenon made up of values and meanings, circumscribed in the social, cultural and historical situation of the subject. The murder of Zé Maria do Tomé means the death of the body. This event generates another body, marked by blood, violence, and the power of its struggles. From 2010 onwards, after the crime, there is an alignment of proposals and demands for struggles around the agencies and disputes over memories about Zé Maria do Tomé, movements such as MST (Movimentos do Sem Terra), MAB (Movimento dos Atingidos por Barragem) , Cáritas Diocesana and the CPT (Pastoral Commission for the Land – Catholic Church), teachers and students linked to UECE (State University of Ceará) and UFC (Federal University of Ceará), civil society collectives, among others, met and created a collective called M21 (Movimento 21 de Abril). This movement became a collective device that corroborated the creation of Zé Maria do Tomé as a martyr of the rural social struggle, building narratives about exemplarity and the donation of his life in favor of a greater good, thus, the fight against Agribusiness. The construction of the presence of Zé Maria do Tomé is a significant symbolic element that is affirmed in the creation of a debate agenda, in the Zé Maria do Tomé Week (10 editions), in the Pilgrimage, in Law 16820 (authored by State Deputy Renato Rosseno, which prohibits the aerial spraying of pesticides in Ceará), public spaces and offices that received their names. Zé Maria do Tomé was an important interlocutor of the conflicts experienced in the countryside, but, in death, in the making of a martyr, he became a symbol of the fight for social and environmental justice in the daily struggle for rights to land, water and life. However, death is not the end, Zé Maria gains another type of body, he becomes an image, a martyr of/for the social struggle. The death of José Maria Filho gave birth to Zé Maria do Tomé.